Assessing Mistake Potential in Writing German Passive Sentences (An Approach of Language Error Analysis) - Mantasiah R.; Yusri Yusri; Arlian Fachrul Syaputra; Femmy Angreany; Hasmawati Hasmawati; Muhammad Anwar (Seminar Nasional LP2M UNM, 2019)
Abstract. The purpose of this study is to identify the types of errors experienced by students in writing German language passivation. The study uses a qualitative approach, especially the language error analysis approach. The data in this study are in the form of the writings of German students. The results showed that there were 4 types of errors experienced by students: 1) werden conjugation was wrong, 2) did not use Partizip Perfekt, 3) errors in the process of declination of articles, 4) errors in writing subjects or objects. One of the mistakes caused by one of them is the interference of the Indonesian language in learning German. Keywords: Passive Voice, Interference, Error Analysis, German Language.